Anti-food and anti-microbial IgG subclass antibodies in inflammatory bowel disease - Jansen, Anke; Mandić, Ana D; Bennek, Eveline; Frehn, Lisa; Verdier, Julien; Tebrügge, Irene; Lutz, Holger; Streetz, Konrad; Trautwein, Christian; Sellge, Gernot (Scandinavian journal of gastroenterology, 2016)
Inflammatory bowel disease (IBD), particularly Crohn's disease (CD), is associated with increased microbial-specific IgG and IgA antibodies, whereas alterations of anti-food antibodies are still disputed. The knowledge about IgG subclass antibodies in IBD is limited. In this study we analysed IgG subclass antibodies specific for nutritional and commensal antigens in IBD patients and controls. Serum IgG1, IgG2, IgG3 and IgG4 specific for wheat and milk extracts, purified ovalbumin, Escherichia coli and Bacteroides fragilis lysates and mannan from Saccharomyces cerevisiae were analysed by ELISA in patients with CD (n = 56), ulcerative colitis (UC; n = 29), acute gastroenteritis/colitis (n = 12) as well as non-inflammatory controls (n = 62). Anti-Saccharomyces cerevisiae antibodies (ASCA) of all IgG subclasses and anti-B. fragilis IgG1 levels were increased in CD patients compared to UC patients and controls. The discriminant validity of ASCA IgG2 and IgG4 was comparable with that of ASCA pan-IgG and IgA, whereas it was inferior for ASCA IgG1/IgG3 and anti-B. fragilis IgG1. Complicated CD defined by the presence of perianal, stricturing or penetrating disease phenotypes was associated with increased ASCA IgG1/IgG3/IgG4, anti-B. fragilis IgG1 and anti-E. coli IgG1 levels. Anti-food IgG subclass levels were not different between IBD patients and controls and did not correlate with food intolerance. In contrast to anti-microbial Abs, food-specific IgG responses were predominately of the IgG4 isotype and all food-specific IgG subclass levels correlated negatively with age. Our study supports the notion that the adaptive immune recognition of food and commensal antigens are differentially regulated.